2016
DOI: 10.3892/mco.2016.837
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of positive lymph node number in early cervical cancer

Abstract: Abstract. The aim of the present study was to investigate whether the number of metastatic lymph nodes (LNs) is an independent prognostic factor for early cervical cancer. The medical records of 163 stage IB-IIA cervical cancer patients, treated with radical hysterectomy with accompanying pelvic and/or para-aortic lymphadenectomy between 1999 and 2007, were retrospectively reviewed. All prognostic factors identified as being significant in the univariate analysis were included in the multivariate analysis usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
0
14
0
2
Order By: Relevance
“…Our patients underwent pelvic lymphadenectomy for pre-brachytherapy staging to tailor the patient’s definitive treatment, as lymph node metastasis is a major prognostic factor in early cervical cancer 28. Furthermore, imaging-based staging using MRI, CT, and/or positron emission tomography coupled with CT remains inferior to surgical assessment of lymph node status 29.…”
Section: Discussionmentioning
confidence: 99%
“…Our patients underwent pelvic lymphadenectomy for pre-brachytherapy staging to tailor the patient’s definitive treatment, as lymph node metastasis is a major prognostic factor in early cervical cancer 28. Furthermore, imaging-based staging using MRI, CT, and/or positron emission tomography coupled with CT remains inferior to surgical assessment of lymph node status 29.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also identified LN involvement as another strongest prognostic factor affecting OS. The value of LN involvement as an important prognostic factor for survival has been reported previously 4 , 6 , 15 , 36 - 38 , 41 , 42 . However, the prognostic role of LN involvement remains unresolved 5 , 14 , 35 , 39 , 40 , 43 .…”
Section: Resultsmentioning
confidence: 61%
“…Further, no signi cant survival difference is observed between patients without metastasis and those with 1-3 metastatic lymph nodes [20]. Park and Bae reported that the 5year OS rates for patients with stage IB-IIA cervical cancer and 0, 1, and ≥2 positive metastatic lymph nodes were 91, 80, and 47%, respectively (P = 0.006) [21]. Inoue and Morita reported that the 5-year OS rates for patients with stage IB-IIB cervical cancer and 0, 1, 2-3, and ≥4 positive metastatic lymph nodes were 89, 81, 41, and 23%, respectively [22].…”
Section: Discussionmentioning
confidence: 99%